Prognosis of palliative treatment for primary tracheal carcinoma: a two-center retrospective study - Hong, Qinyan; Teng, Jun; Luo, Yi; Wang, Zhina; Zou, Heng; Li, Lei; Zhang, Nan; Wang, Hongwu (Frontiers in Oncology, 2025)
IntroductionMore than half of patients with tracheal carcinoma (TC) do not receive radical treatment, but the clinical characteristics, palliative treatment options, and prognosis of this group remain unclear.MethodsThis retrospective study analyzed 94 single primary TC patients (42 with tracheal squamous cell carcinoma [TSCC] and 52 with tracheal adenoid cystic carcinoma [TACC]) admitted to the Emergency General Hospital and Dongzhimen Hospital, Beijing University of Chinese Medicine. Kaplan-Meier survival curves, Log-rank tests, univariate and multivariate Cox and AFT models were used to assess overall survival (OS).ResultsAmong 89 patients without radical treatment, the median survival was 57 months, with 5-year and 10-year survival rates of 46.33% and 13.43%, respectively. Univariate analysis identified pathological type, smoking history, initial tumor extension (ITE), and targeted therapy as significant prognostic factors. The AFT model revealed that the median OS for TSCC patients was significantly shorter than for TACC patients, with a time ratio (TR) of 0.243 (95% CI: 0.153-0.386; P < 0.01), while targeted therapy was associated with a 1.790-fold increase in OS (TR: 1.790, 95% CI: 1.061-3.020; P = 0.029). Patients with extensive ITE had worse outcomes, with a TR of 0.628 (95% CI: 0.406-0.971; P = 0.037). Smokers had a TR of 0.601 (95% CI: 0.397-0.912; P = 0.017) compared with non-smokers. Subgroup analysis showed that smoking history was strongly associated with shorter OS in TSCC but not in TACC.ConclusionsPathological type, ITE, targeted therapy and smoking history are important factors for evaluating the prognosis of TC patients receiving palliative treatment.